Development of Guided Inquiry-Based Thermodynamics Devices Integrated With Pottery Making Local Wisdom to Enhance Computational Thinking - Reny Afifah; Jumadi Jumadi; Ayu Ayu Mar'ati Barokatin Ni'mah; Supahar Supahar (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
Students' computational thinking ability can be improved by using guided inquiry learning integrated with the local wisdom of the pottery-making process. This research aims to: (1) produce physics learning devices integrated with the process of making pottery on thermodynamic material that are feasible to use and valid and reliable instruments to improve students' computational thinking skills; (2) determine the effectiveness of physics learning devices integrated with the process of making pottery on thermodynamic material to improve students' computational thinking skills. This research uses the ADDIE model. The instrument used was the computational thinking ability test. The quality of learning devices was analyzed using descriptive analysis, which became the basis for revising teaching devices. Quantitative data were obtained from the validation results of instrument computational thinking ability questions by experts and practitioners. The results showed that: (1) physics learning devices integrated with the process of making pottery on the material of thermodynamics. (1) learning devices for thermodynamics integrated with the local wisdom of pottery making are feasible to use to improve computational thinking skills; (2) Thermodynamic learning devices integrated with local wisdom of pottery making are effectively used to improve computational thinking skills.